Diversity of the diet is correlated with osteoporosis in post-menopausal women: an Iranian case-control study - Abbasi, Behnood; Hajinasab, Mohammad Mahdi; Mohammadi Zadeh, Zahra; Ahmadi, Paniz (Frontiers in Public Health, 2024)
Background: Proper nutrition is a crucial factor in preventing osteoporosis, a significant pathological cause linked to skeletal weakness; this study investigated the relationship between dietary diversity score and food group diversity score with osteoporosis in postmenopausal women. Methods: This case-control study was conducted on 378 menopausal women aged 45 to 85 in Tehran, Iran. The age-matching method to control the confounding effect of age was used. The method of dual-energy X-ray absorptiometry (DXA) was used for assessing the bone mineral density of lumbar vertebrae and femoral neck. The bone mass status was evaluated with WHO criteria. All subjects were divided into the osteoporosis group and the non-osteoporosis group according to their T-score. A convenience sampling method was utilized to select the participants, which included two groups: case (n=189) and control (n=189). Data was collected using demographic and anthropometric information questionnaires, a valid 147 item food frequency questionnaire, and a physical activity questionnaire. Statistical analyses were conducted using SPSS-26, and P-values less than 0.05 were deemed to be statistically significant.The results indicated significant differences in weight, body mass index, physical activity, smoking, and alcohol use between the two groups. The mean±standard deviation of dietary diversity score (DDS) was lower in participants with osteoporosis (case) (3.31 ± 1.26) than in control (4.64 ± 1.33) (P<0.001). The mean±standard deviation of diversity score of cereals, fruits, and vegetables in the osteoporosis group (respectively: 0.71 ± 0.21, 0.94 ± 0.76, and 0.45 ± 0.44) was less than the control group (respectively: 0.80 ± 0.21, 1.64 ± 0.55 and 0.87 ± 0.42) (P<0.001). After adjusting the confounding variables, the risk of osteoporosis had an inverse relationship with the diversity score of vegetable (OR= 0.16; 95%CI: 0.07-0.35), bread and cereal (OR= 0.21; 95% CI: 0.05-0.87) and fruit (OR= 0.35; 95%CI: 0.22-0.56) (P<0.05). Nevertheless, no discernible correlation was seen between the tertiles of DDS, dairy and meat diversity score, and osteoporosis.We found a correlation between the diversity score of fruits, vegetables, and grains and osteoporosis. However, there is no significant correlation between the DDS triads and the diversity score of dairy products and meats with osteoporosis.